A computational grammar for Portuguese - Claro, Bruno Cuconato (2019)
In this work we present a freely-available type-theoretical computational grammar for Portuguese, implemented in the Grammatical Framework (GF) multilingual formalism. Such a grammar can be used for both syntactic parsing and natural language generation. We first describe the formalism itself, discussing its logico-mathematical foundations; we then present our grammar. We evaluate our grammar’s productions with respect to syntactical correctness, show possible applications, and discuss future work.